Influence of atopic dermatitis on the quality of life of young children (Texas Journal of Medical Science, 2024)
The study of QoL in pediatrics is of undoubted interest, as this opens up the possibility of a comprehensive analysis and study of the child's health. The use of indicators of the quality of life in the practice of a doctor can become an additional criterion for assessing the state of health and development of the child, the effect of the disease on the well-being of the child, as well as assessing the effectiveness of therapy